Implementation of the Scramble Learning Model and Its Effect on Student Motivation and Learning Outcomes - Yeni Rostiana; Ali Imran (PAIDAGOGIA: Jurnal Inovasi Pendidikan dan Pembelajaran, 2024)
This study aims to determine the effect of the scramble learning model on student motivation and learning outcomes. The research employed a Quasi-Experimental design using a Pretest-Posttest Control Group. The population consisted of all eighth-grade students at MTs Ulil Al-Baab NW Lendang Jaran, East Lombok, with a sample size of 40 students. Student learning outcomes data were collected using tests, while motivation data were gathered using questionnaires. The data were analyzed using descriptive statistics and a t-test to determine the differences in student learning outcomes between the experimental and control groups. The implementation of the scramble learning model had a positive impact on improving student learning outcomes. This was reinforced by significant differences in student learning outcomes between the experimental and control groups (p>0.05). The influence of the Scramble learning model is presumed to be due to its offering of interactive and collaborative learning activities, ultimately enhancing student learning outcomes. Additionally, the research findings indicate that the Scramble learning model affects student motivation. Further findings reveal that student motivation in the experimental and control groups does not significantly differ, likely due to intrinsic factors such as interest in learning. This is supported by observational results showing no significant difference in student interest in learning between the experimental and control groups, suggesting that student motivation in both groups is not significantly different.